Deacylcynaropicrin Inhibits RANKL-Induced Osteoclastogenesis by Inhibiting NF-κB and MAPK and Promoting M2 Polarization of Macrophages - Li, Zhikun; Zhu, Xiaodong; Xu, Ruijun; Wang, Yi; Hu, Ruixi; Xu, Wei (Frontiers in Pharmacology, 2019)
Inflammation can promote the mature of osteoclasts and the bone resorption in many bone disease such as osteoporosis and arthritis. Here, we aimed to investigate the inhibitory effects of deacylcynaropicrin (DAC) on osteoclastogenesis and bone resorption induced by RANKL. Bone marrow-derived monocytes and RAW264.7 cells were used for assessing the influence of DAC on polarization of macrophages and osteoclastogenesis in vitro. Inducible nitric oxide synthase (iNOS) and CD206, and osteoclastogenesis markers, nuclear factor of activated T-cells 1 (NFATc1) and c-Fos, were qualitatively analyzed by immunofluorescence, flow cytometry, reverse transcription polymerase chain reaction, and western blotting. The results showed that DAC significantly inhibited osteoclastogenesis by suppressing the expression levels of c-Fos and NFATc1 through nuclear factor-κB, c-Jun N-terminal kinase (JNK), and Akt pathway. Moreover, immunohistochemistry and enzyme-linked immunosorbent assays showed that DAC reduced the release of tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 in vivo. Finally, DAC also promoted macrophage polarization from M1 to M2 types. In conclusion, these results demonstrated that DAC suppressed RANKL-induced inflammation and osteoclastogenesis and therefore it can be used as a potential treatment for osteoporosis, arthritis, ostelysis and aseptic loosening of artificial prostheses.